2011
DOI: 10.2131/jts.36.31
|View full text |Cite
|
Sign up to set email alerts
|

Depression-related anhedonic behaviors caused by immobilization stress: a comparison with nicotine-induced depression-like behavioral alterations and effects of nicotine and/or "antidepressant" drugs

Abstract: -Anhedonia, an affective symptom related to the inability to experience pleasure, is one of the representative symptoms observed in depression. In the present study, considering that repeated nicotine (NC) also causes "depressive" symptoms, the depression-related anhedonic behavioral alterations caused by a typical depression-inducing stressor, immobilization stress (IM), combined with or without NC administration, were examined in mice and compared with the depression-like behavioral alterations caused by NC.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 45 publications
(81 reference statements)
6
18
0
Order By: Relevance
“…Depression like behavioral alteration can be produced by the stressors such as immobilization stress (Hyase, 2011). The results of the present study showed that the immobilization stress enhanced the immobility period of the mice in both TST and FST significantly as compared to the vehicle treated unstressed mice.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Depression like behavioral alteration can be produced by the stressors such as immobilization stress (Hyase, 2011). The results of the present study showed that the immobilization stress enhanced the immobility period of the mice in both TST and FST significantly as compared to the vehicle treated unstressed mice.…”
Section: Discussionsupporting
confidence: 46%
“…Stress induces depression like behavioral alteration in the laboratory animals subjected to the stress (Hyase, 2011). Depression like behavioral alteration in the laboratory animals can be measure by using TST and FST (Porsolt et al, 1977;Steru et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many concerns exist about the risks of using a potentially hazardous chemical to treat AD patients (Baldinger and Schroeder, 1995). Similarly, literature surveying the effect of nicotine on depressive-like behavior is ambivalent with some preclinical studies reporting decreased (Djuric et al, 1999; Semba and Wakuta, 2008) or increased (Hayase, 2007, 2008, 2011, 2013) depressive behavior with nicotine use.…”
Section: Discussionmentioning
confidence: 99%
“…All parameters were analyzed automatically by the ActiMot software (TSE, Bad Homburg, Germany) as described before (Brzozka et al 2011). Anhedonia was evaluated by tail suspension test as described (Hayase T, 2011). Briefly, a cube of 35 cm each side with an open front was used to perform the experiment.…”
Section: Methodsmentioning
confidence: 99%